Two-photon absorption of ligand-protected Ag15 nanoclusters. Towards a new class of nonlinear optics nanomaterials. Issue 18 (29th January 2016) - Sanader, Željka; Krstić, Marjan; Russier-Antoine, Isabelle; Bertorelle, Franck; Dugourd, Philippe; Brevet, Pierre-François; Antoine, Rodolphe; Bonačić-Koutecký, Vlasta
Abstract : Theoretical and experimental two-photon absorption cross sections of thiolated small silver cluster Ag15 L11 exhibiting extraordinary large TPA. Abstract : We report theoretical and experimental results on two-photon absorption (TPA) cross section of thiolated small silver cluster Ag15 L11 exhibiting extraordinary large TPA in red. Our findings provide the responsible mechanism and allow proposing new classes of nanoclusters with large TPAs which are promising for biological and medical applications.